FOREIGN EXPERIENCE IN ASSESSING THE EXPORT POTENTIAL OF THE CHEMICAL INDUSTRY (World Economics and Finance Bulletin, 2022)
This article examines the state and development of the chemical industry in foreign countries such as Germany, China and the United States. Analyzed the main products of the chemical industry, their production, trade, value added, the state of enterprises, exports, imports and trade balance of countries in the trade of chemicals.
Keywords: Chemical industry; manufacture; foreign trade; product